2003
DOI: 10.1177/08830738030180041101
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Prolonged Afterdischarges in Children With Malformations of Cortical Development

Abstract: We investigated aberrant cortical excitability in malformations of cortical development From subdural electrodes, we recorded afterdischarges lasting > or = 6 seconds in 12 of 13 patients with malformations of cortical development and 6 of 10 pediatric patients with nonmalformations of cortical development and reviewed amperage thresholds, distribution of afterdischarges, and motor responses. In patients with malformation of cortical development, motor response thresholds were high; afterdischarge and motor re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Postnatal maturation influences the expression of dysplastic hyperexcitability, as afterdischarge thresholds show a steep decline with age (Jayakar et al., 1992; Chitoku et al., 2003). Younger patients evidence remote afterdischarges distant to the stimulation site (Chitoku et al., 2003).…”
Section: Dysplastic Cortex Is Intrinsically Hyperexcitablementioning
confidence: 99%
“…Postnatal maturation influences the expression of dysplastic hyperexcitability, as afterdischarge thresholds show a steep decline with age (Jayakar et al., 1992; Chitoku et al., 2003). Younger patients evidence remote afterdischarges distant to the stimulation site (Chitoku et al., 2003).…”
Section: Dysplastic Cortex Is Intrinsically Hyperexcitablementioning
confidence: 99%
“…We defined an epileptic zone as the place where synchronized spike discharges were seen at three or more ECoG electrodes. 7,29 Patients with lesions or interictal zones around the central sulcus underwent intraoperative median nerve electrical stimulation to identify the SSEP N20 component.…”
Section: Intraoperative Ecog Extraoperative Iveeg and Surgical Procmentioning
confidence: 99%
“…In fact, it has been shown that prolonged after-discharges occur more frequently in patients with neuronal migration disorders than in patients with other epileptic disorders. 41 Therefore, a decrease in the local excitability in the area with cortical dysplasia may result in a decrease of the abnormal excitatory input to the normal, healthy surrounding cortex that ultimately results in an increase of the inhibitory drive to the dysplastic cells. Because rTMS may disrupt this pathological excitatory network, the reestablishment of the normal activity is possible.…”
mentioning
confidence: 99%